Ylang Flower Gel Antifungal Effectiveness - Ariyanti Ariyanti; Eni Masruriati; Dwi Setyowati; Filza Mazaya Nurulita (GLOBAL HEALTH SCIENCE GROUP, 2022)
Ylang flower (Cananga odorata) has effectiveness as an antibacterial and antifungal because the ylang flower plant contains the main compounds, namely -linalool (12.8%), -caryophyllene (8.99%), farsenol (6.8%), germacren- D (5.35%), -bergamotene (8.45%), and benzyl benzoate (5.9%). The substances contained in ylang flower essential oil are alcohol (53% - 65%) with methylbenzoate esters, linalool esters, and terpineol esters, sesquiterpenes which have anti-inflammatory, antimicrobial, antioxidant properties, and also prevent bacteria and germs and have anti-inflammatory activity. local anesthetic. The essential oil of ylang flower has antibacterial properties because the substances contained therein are in the form of an active component called kariofilen. This karyophylene compound has anti-inflammatory, antimicrobial and germ-preventing properties. This study was conducted to determine the effectiveness of the antifungal contained in the gel from ylang flower (Cananga odorata) using the disc diffusion method, which is the method used in microbial testing, and to determine the concentration of hydroxy propyl methyl cellulose (HPMC) with the addition of propylene glycol used. as a humectant in order to maintain the stability of the gel preparation on physical properties and the effectiveness of ylang flower essential oil as an antifungal by making a gel preparation. The essential oil gel from ylang flower was used as a test of the physical properties of the gel (pH, viscosity, homogeneity, dispersion and adhesion). The results of the research that have been carried out prove that the gel formula from ylang flower extraction using HPMC base with a concentration of 5% has good physical properties of the gel because it is seen in the organoleptic test, pH test, viscosity, homogeneity, dispersion and adhesion meet the specified requirements. in stock. It can be concluded in this study that the gel preparation of ylang flower has antifungal activity or can inhibit the presence of M.furfur fungus from a gel based on HPMC with a concentration of 5% has good gel physical properties and better antifungal activity compared to gel which has a better concentration 10% and 15%.